FORMULASI KRIM EKSTRAK RIMPANG RUMPUT TEKI (Cyperus rotundus) DAN UJI AKTIVITAS ANTIBAKTERINYA TERHADAP Staphylococcus aureus ATCC 25923 - Fatmah Estu Lamaga; Hikmatun Nazila; Raodatul Fitri; Filu Marwati Santoso Putri (Jurnal Kesehatan Madani Medika (JKMM), 2019)
Cyperus rotundus L. is one of the plants that can be used as a traditional medicine. This rhizome contains essential oils that have potential as antibiotics against Staphylococcus aureus bacteria. Some of the infections caused by this gram-positive bacteria are abcess, acne, impetigo, and scarring infections. The ease of use and effectiveness Cyperus rotundus L. rhizome on the skin as the antibacterial could be improved by formulating in cream preparations. This study aims to determine the effect of the cream base on the physical properties of the cream and the antibacterial acitivity of the Cyperus rotundus L. rhizome ethanol extract on Staphylococcus aureus. This type of research is experimental research, using the diffusion method and the diameter of the inhibition zone. The physical properties of the cream (organoleptic, dispersion, adhesion and protection ability) and antibacterial activity were tested in this study. The analysis used in this research is descriptive analysis. The results showed that cream of the ethanol extract of Cyperus rotundus rhizome at a concentration of 5%, 7.5%, and 10% has a good physical/organoleptic appearance, spreadability, and good protective ability. Meanwhile, the entire cream of the Cyperus rotundus L. rhizome ethanol extract showed poor adhesion. The cream of ethanol extract of Cyperus rotundus L. rhizome showed antibacterial activity against Staphylococcus aureus ATCC 25923 at concentrations of 10%.